Genus Lepidozonates Park (Lepidoptera, Lecithoceridae) from China, with description of a new species - Yu, Shuai; Wang, Shuxia (Zootaxa, 2021)
Four species of the genus Lepidozonates Park, 2013 are reviewed in China. Lepidozonates semiovatus sp. nov. is described as new; L. prominens Park, 2013 and L. tenebrosellus Park, 2013 are newly recorded in China; Philharmonia adusta Park, 2000 is transferred to the genus Lepidozonates as L. adusta comb. nov.; and L. viciniolus Park, 2013 syn. nov. is proposed as a new synonym of P. adusta. The female of L. tenebrosellus is described for the first time. Images of adults and genitalia of the Chinese species are provided, along with a key to all the five species of Lepidozonates.